FRAMING DETIK.COM DAN LIPUTAN6.COM TERHADAP CITRA POLITIK RIDWAN KAMIL DALAM ISU KORUPSI BJB - Rambe , Ahmad Sampurna; Fatika, Annisa; Syahputra , Roni; Deansyah , Reti Miranda; Syahputra , Andra; Purnama, Rahma Aulia Sukma (AT-TAWASUL, 2025)
This study aims to analyze the media framing by Detik.com and Liputan6.com regarding the political image of Ridwan Kamil in the context of the alleged Bank Pembangunan Daerah Jawa Barat dan Banten (BJB) corruption case. The issue attracted public attention due to Ridwan Kamil's position as President Commissioner of Bank Pembangunan Daerah Jawa Barat dan Banten (BJB), making it politically significant. The research employs a qualitative descriptive approach using Robert N. Entman’s framing analysis model, which includes four key elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. Data were collected through documentation of online news articles published by both media outlets up to May 2025. The findings reveal that Detik.com tends to frame the issue explicitly and with a sensational tone, highlighting Ridwan Kamil as a central figure in the case and thus shaping a negative perception of his integrity and credibility. In contrast, Liputan6.com reports the issue more neutrally and procedurally, portraying Ridwan Kamil as someone not yet proven legally involved, and maintaining balanced information to avoid premature public judgment. This contrast in framing significantly affects the construction of Ridwan Kamil's political image in the digital public sphere. The study concludes that media plays a crucial role in shaping public perception of political figures, and that framing choices can substantially influence a leader’s perceived integrity, capability, and credibility